(untitled) (Innovaciones Educativas, 2023)
A systematization of experience is presented, carried out by the Chair of Special Education of the Universidad Estatal a Distancia (Costa Rica) in collaboration with the Universidad Villanueva de Madrid (Spain), aimed at improving the development of Early Childhood Care (ECE) in Costa Rica (CR), through a teacher training program in the care of children from 0 to 6 years of age with developmental disorders or at risk of presenting them, considering the differential cultural context of each country and the role of parents and other professionals in child development. For this purpose, a study is presented under a qualitative perspective and with a descriptive-interpretative approach. This innovation experience was systematized in four phases: the first, carried out jointly by both universities, aimed at studying, identifying and detecting the TA training needs of teachers in CR; the second, the planning and design of the experience; the third, its implementation by TA professionals in Spain, aimed at preschool teachers, families and EBAIS specialists; the fourth phase, also collaborative, consists of the analysis, evaluation and reflection of the experience. The results show the need to establish a global action plan in CR that allows for the organizational development of ECI. It confirms the need for teacher training as a mediating vehicle for working with families to favor their empowerment and multiply their children’s learning opportunities.